Knowledge Sharing, Innovation Capability, Responsive Capability, and Marketing Performance: an Empirical Study at UPN “Veteran” Jawa Timur - Rangga Restu Prayogo; Lia Nirawati (School of Business, IPB University (SB-IPB), 2019)
Business organizations are required to be able to do effective marketing. Market change demands a business organization to have a marketing capability on innovation and responses in making a product to be competitive; therefore, it should create a quality product. Creating a quality product is influenced by the knowledge of products to be created so as to produce good marketing performance. The purposes of this study were to see how big an influence towards knowledge sharing innovation capability, and to identify the capability to respond to the market and performance marketing. A questionnaire was given to students who were in the university environment by using purposive sampling with accidental sampling. Reliability and validity were measured through the median and variation analysis of Cronbach's alpha, and Analysis using SEM model structure with SMARTPLS was used to test the relationship between research variables using 100 respondents. The results showed that sharing knowledge has a positive and significant effect on the capabilities of innovation and responsive capabilities, but insignificant effect on marketing performance. The responsive capability of innovation and capability on marketing performance are positive and significant.Keywords: knowledge sharing, marketing capability, innovation capability, responsive capability, marketing performance